Biodegradation of PAHs by Bacillus marsiflavi, genome analysis and its plant growth promoting potential. (1st January 2022) - Saeed, Maimona; Ilyas, Noshin; Bibi, Fatima; Jayachandran, Krish; Dattamudi, Sanku; Elgorban, Abdallah M.
Abstract: The biodegradation of hazardous petroleum hydrocarbons has recently received a lot of attention because of its many possible applications. Bacillus marsiflavi strain was isolated from oil contaminated soil of Rawalpindi, Pakistan. Initial sequencing was done by 16s rRNA sequencing technique. Bac 144 had shown 78% emulsification index and 72% hydrophobicity content. Further, the strain displayed production of 15.5 mg/L phosphate sloubilization and 30.25 μg/ml indole acetic acid (IAA) in vitro assay. The strain showed 65% biodegradation of crude oil within 5 days by using Gas Chromatography-Mass Spectrometry (GC-MS) analysis. Whole Genome analysis of Bac 144 was performed by PacBio sequencing and results indicated that Bacillus marsiflavi Bac144 strain consisted of size of 4, 417, 505bp with closest neighbor Bacillus cereus ATCC 14579. The number of the coding sequence was 4662 and number of RNAs was 141. The GC content comprised 48.1%. Various genes were detected in genome responsible for hydrocarbon degradation and plant defense mechanism. The toxic effect of petroleum hydrocarbons in soil and its mitigation with Bac 144 was tested by soil experiment with three levels of oil contamination (5%, 10% and 15%). Soil enzymatic activity such as dehydrogenase and fluorescein diacetate (FDA) increased up to 49% and 40% with inoculation of Bac 144, which was considered to be correlated with hydrocarbon degradation recorded as 46%. An increase of 20%, 14% and 9% in shoot length of plant at 5%, 10% and 15% level of oil was recorded treated with Bac 144 as compared to untreated plants. A percent increase of 14.89%, 16.85%, and 13.87% in chlorophyll, carotenoid, and proline content of plant was observed by inoculation with Bac 144 under oil stress. Significant reduction of 14% and 18%, 21% was recorded in the malondialdehyde content of plant due to inoculation of Bac 144. A considerable increase of 21.33%, 19.5%, and 24.5% in super oxide dismutase, catalase, and peroxidase dismutase activity was also observed in plants inoculated with strain Bac 144. These findings suggested that Bac-144 can be considered as efficient candidate for bioremediation of hydrocarbons. Highlights: Bacillus marsiflavi Bac 144 strain was isolated from oil contaminated soil of Rawalpindi, Pakistan which showed plant growth-promoting attributes. Whole genome sequencing of strain indicated the presence of genes involved in hydrocarbon degradation. Bac 144 had shown a positive impact on the growth of maize plant and hydrocarbon degradation at three levels of oil contamination (5%, 10% and 15%).